Towards understanding governance issues in integration of mental health into primary health care in Uganda. Issue 1 (December 2016) - Mugisha, James; Ssebunnya, Joshua; Kigozi, Fred
Abstract Background There is a growing burden of mental illness in low income countries. The situation is further worsened by the high poverty levels in these countries, resulting in difficult choices for their health sectors as regards to responding to the burden of mental health problems. In Uganda, integration of mental health into primary health care (PHC) has been adopted as the most vital strategy for ensuring mental health service delivery to the general population. Objectives To identify governance related factors that promote/or hinder integration of mental health into PHC in Uganda. Methods A qualitative research design was adopted at national and district level. A total of 18 Key informant interviews were conducted at both levels. Content thematic analysis was the main method of data analysis. Findings There were positive gains in working on relevant laws and policies. However, both the mental health law and policy are still in draft form. There is also increased responsiveness/participation of key stakeholders; especially at national level in the planning and budgeting for mental health services. This however seems to be a challenge at both district and community level. In terms of efficiency, human resources, finances, medicines and technologies constitute a major drawback to the integration of mental health into PHC. Ethics, oversight, information and monitoring functions though reported to be in place, become weaker at the district level than at national level due to limited finances, human resources gaps and limited technical capacity. Other governance related issues are also reported in this study. Conclusions There is some progress especially in the legal and policy arena to support integration of mental health into PHC in Uganda. However, adequate resources are still required to facilitate the effective functioning of all governance pillars that make integration of mental health into PHC feasible in Uganda.